Modified application of Kawamoto’s film method for super‐resolution imaging of megakaryocytes in undecalcified bone marrow - Morodomi, Yosuke (Res Pract Thromb Haemost, 2019)
BACKGROUND: Super‐resolution microscopy has enabled high‐resolution imaging of the actin cytoskeleton in megakaryocytes and platelets. These technologies have extended our knowledge of thrombopoiesis and platelet spreading using megakaryocytes and platelets cultured in vitro on matrix proteins. However, for better understanding of megakaryocytopoiesis and platelet production, high‐resolution imaging of cells in an in vivo bone marrow microenvironment is required. Development of Kawamoto’s film method greatly advanced the techniques of thin cryosectioning of hard tissues such as undecalcified bones. One obstacle that remains is the spherical aberration that occurs due to the difference in the refractive index for the light path, limiting the usage of Kawamoto’s film method to lower magnification observation. OBJECTIVES: To overcome the weakness of the conventional Kawamoto’s film method for higher magnification observation of undecalcified bone marrow. METHODS: We have modified the original method with a very simple method: flipping the film at the step of mounting the sections on the glass. RESULTS AND CONCLUSIONS: This new method successfully led to the adjustment of the refractive index and enabled super‐resolution imaging of megakaryocytes in undecalcified mouse femurs. Our modified method will expand the application of Kawamoto’s film method and enable precise analysis of megakaryocytopoiesis and platelet production in the bone marrow microenvironment under pathophysiological conditions.